2015
DOI: 10.1016/j.toxrep.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Campomanesia adamantium (Myrtaceae) fruits protect HEPG2 cells against carbon tetrachloride-induced toxicity

Abstract: Campomanesia adamantium (Myrtaceae) is an antioxidant compounds-rich Brazilian fruit popularly known as gabiroba. In view of this, it was evaluated the hepatoprotective effects of pulp (GPE) or peel/seed (GPSE) hydroalcoholic extracts of gabiroba on injured liver-derived HepG2 cells by CCl4 (4 mM). The results showed the presence of total phenolic in GPSE was (60%) higher when compared to GPE, associated with interesting antioxidant activity using DPPH• assay. Additionally, HPLC chromatograms and thin layer ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
0
22
1
3
Order By: Relevance
“…Each cell line was cultured in complete Dulbecco's Modified Eagle's Medium (DMEM, Sigma-Aldrich, St. Louis, MO, USA), supplemented with 20% (v/v) fetal bovine serum (FBS) (GIBCO-Invitrogen, Indianapolis, IN, USA), solution containing penicillin (100 IU/mL) and streptomycin (100  μ g/mL) (Sigma-Aldrich, St. Louis, MO, USA), and 2  μ g/mL amphotericin B (Sigma-Aldrich, St. Louis, MO, USA). The cells were kept in an incubator (Panasonic®, Chicago, IL, USA) in a humidified atmosphere of 5% CO 2 in air at 37°C [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…Each cell line was cultured in complete Dulbecco's Modified Eagle's Medium (DMEM, Sigma-Aldrich, St. Louis, MO, USA), supplemented with 20% (v/v) fetal bovine serum (FBS) (GIBCO-Invitrogen, Indianapolis, IN, USA), solution containing penicillin (100 IU/mL) and streptomycin (100  μ g/mL) (Sigma-Aldrich, St. Louis, MO, USA), and 2  μ g/mL amphotericin B (Sigma-Aldrich, St. Louis, MO, USA). The cells were kept in an incubator (Panasonic®, Chicago, IL, USA) in a humidified atmosphere of 5% CO 2 in air at 37°C [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…C. adamantium (Myrtaceae) is an antioxidant fruit, and results showed the hepatoprotective effects of pulp or peel/seed hydroalcoholic extracts on injured liverderived HepG2 cells by CCl4. The results in part are associated with the presence of antioxidant compounds, especially flavonoids [16]. Researches and studies prove that the oleic and linoleic fatty acids obtained from the oil of the seeds from C. xanthocarpa Berg.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit pulp has greater technological applicability than any other part. Its peel and seeds are considered industrial residue; on the other hand, studies have shown that this sample has great effectiveness antioxidant protection in cells, thanks to its bioactive compounds (Alves, Alves, Fernandes, Naves, & Naves, 2013; de Oliveira Fernandes, Ávila, Moura, Ribeiro, Naves, & Valadares, 2015). No evidence of toxicity was found in the fruit peel, so it is considered safe to be part of the human diet.…”
Section: Introductionmentioning
confidence: 99%